Thismia: the rarest of the rare? Ranges of some Bornean species are much larger than previously believed - Dančák, Martin; Hroneš, Michal; Sochor, Michal (Phytotaxa, 2020)
Fairy lanterns (Thismia; Thismiaceae, Dioscoreales) are believed to be extremely rare and narrowly endemic plants. Despite that, many new Thismia populations have been recently discovered in Borneo. These are summarized and discussed here and all twelve Bornean Thismia species with multiple localities are reviewed. New localities of T. brunneomitra, T. hexagona, T. neptunis, T. pallida and T. viridistriata are reported which considerably enlarge ranges of these species. New conservational statuses are proposed for T. brunneomitra, T. goodii, T. hexagona and T. neptunis. New or unpublished localities are also reported for T. cornuta and T. goodii. Although the known within-species morphological variability is extended only little or not at all by these finds, geographically distant populations often exhibit relatively large genetic differences, in some cases similar to those among distinct species (namely T. brunneomitra and T. minutissima). The new data show that, at least in some tropical species of Thismia, we can expect quite normal type of distribution with multiple localities over relatively large geographical areas.